New Diagnostic Method for Fetal Membrane Premature Rupture - Kuzmina, I. Yu. (Problems of Cryobiology and Cryomedicine, 2008)
Premature rupture of fetal membranes in pregnant women has been diagnosed at different gestation terms. The application of ALREKAH lining was proved as enabling to determine the amniotic membrane leakage in 100% cases.